The Effect of Training and Career Development on Company Performance: A Systematic Literature Review - Fabian, Natanael Tio; Kirani, Agnes Neisha; Dewi, Puja Kalima; Gracia, Ribka; Loei, Jonathan; Muyandi, Muhammad Rachman; Kalfin (Communication in Research and Publications (CRP), 2024)
Company performance in the business era is something that needs to be considered in maintaining the continuity of a company. Training and career development are one of the variables that affect company performance. Therefore, this study will look at the effect of training and career development on employee performance based on literature review. In this study using article data that has been published in google scholar indexed journals from 2013-2023. This study uses a systematic literature review method in obtaining the expected results. Based on the results of the analysis obtained that training and career development have a role in improving employee performance. Training on employee performance has an important relationship. With training, employees can develop skills, as well as various kinds of new knowledge. Along with the training conducted by the company, the performance produced by employees will also increase which will affect the development of the company. Likewise, with career development in the company, it will trigger employee enthusiasm to work harder, motivate employees, and attract employees to work for a long time in the company. Based on the results of this study, it is hoped that it can be a reference for companies in improving employee performance. Of course, by paying attention to variables of training and career development.